Survei Status Gizi Dan Kebugaran Jasmani Terhadap Aktivitas Fisik Pada Mata Kuliah Praktek Mahasiswa Penjaskesrek STKIP Yapis Dompu. - Iman Zulfikar; Taufik Hidayat; Linda Susila; M. Amin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
This research was conducted in the Physical Education, Health and Recreation (Penjaskesrek) Study Program of STKIP Yapis Dompu,with the goal of determining the level of nutritional status and physical fitness of Penjaskesrek students at STKIP Yapis Dompu in the year 2024 in the following practical courses. The research method used a quantitative descriptive study, and the sampling technique used purposive sampling with a total sample of 52 students in semester 3. The nutritional status measurement instrument employs test items for body mass index (IMT) and physical fitness tests (VO2Max), as well as the multistage fitness test (bleep). The results of IMT measurements were 2 students or 3.84% at the less / malnutrition level, 39 or 75% in the normal weight category, 7 or 13.46% of students in the overweight category, and 4 students or 7.69% had more weight / obesity. While the results of research on physical fitness (VO2Max) dominant students in the moderate category as many as 22 or 46.15% of students, 16 students or 30.76% in the lesser category, 4 students or 11.51% in the less category, 8 students or 19.23% in the good category, and 2 students 3.83% in the excellent category.